2023
DOI: 10.1093/sleep/zsad055
|View full text |Cite|
|
Sign up to set email alerts
|

Sympathetic dysregulation induced by postnatal intermittent hypoxia

Abstract: Study objectives Exposure to postnatal chronic intermittent hypoxia (pCIH), as experienced in sleep-disordered breathing, is a risk factor for developing cardiorespiratory diseases in adulthood. pCIH causes respiratory instability and motor dysfunction that persist until adult life. In this study, we investigated the impact of pCIH on the sympathetic control of arterial pressure in rats. Methods and Results Neonate male Holtz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Neurons in the NTS relay information to the hypothalamic paraventricular nucleus and sympathoexcitatory neurons in the RVLM (Herman & Cullinan, 1997;Sawchenko et al, 1996). A recent study reported that IH increases RVLM neuronal activity linked to presympathetic neurons (Karlen-Amarante et al, 2023). On the one hand, Zoccal et al (2011) believe that IH enhances purinergic but not glutamatergic transmission in the RVLM.…”
Section: Effect Of Ih On the Central Component Of The Carotid Body Ch...mentioning
confidence: 99%
“…Neurons in the NTS relay information to the hypothalamic paraventricular nucleus and sympathoexcitatory neurons in the RVLM (Herman & Cullinan, 1997;Sawchenko et al, 1996). A recent study reported that IH increases RVLM neuronal activity linked to presympathetic neurons (Karlen-Amarante et al, 2023). On the one hand, Zoccal et al (2011) believe that IH enhances purinergic but not glutamatergic transmission in the RVLM.…”
Section: Effect Of Ih On the Central Component Of The Carotid Body Ch...mentioning
confidence: 99%
“…While animal models cannot fully recapitulate the complexity of the clinical scenario, CIH models do produce an injury profile similar to that seen in humans, with respect to white matter loss, neurodevelopmental delay, and functional deficits [[11], [13]]. Very recently, it has been suggested that postnatal CIH might be a risk factor for developing cardiorespiratory diseases in adulthood as well [[64]]. The models generally involve several daily sessions of intermittent hypoxia over various days [[65]].…”
Section: Consequences Of Cih On Cerebrovascular Structure and Functionmentioning
confidence: 99%
“…In rats, CIH increases sympathetic activity and disrupts respiratory-sympathetic coupling resulting in hypertension ( Zoccal et al, 2008 ; Simms et al, 2009 ; Zoccal et al, 2009 ; Molkov et al, 2011 ). Furthermore, when exposure to CIH occurs postnatally, elevated arterial pressure levels and baroreflex dysfunctions can persist into adulthood ( Soukhova-O'Hare et al, 2006 ; Karlen-Amarante et al, 2023 ). The cardiopulmonary effects of CIH have been attributed to the overexcitation of rostral ventrolateral medulla (RVLM) presympathetic neurons ( Karlen-Amarante et al, 2023 ) via excitatory and inhibitory inputs from respiratory rhythmogenic networks ( Lipski et al, 1996 ; Molkov et al, 2011 ; Moraes et al, 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when exposure to CIH occurs postnatally, elevated arterial pressure levels and baroreflex dysfunctions can persist into adulthood ( Soukhova-O'Hare et al, 2006 ; Karlen-Amarante et al, 2023 ). The cardiopulmonary effects of CIH have been attributed to the overexcitation of rostral ventrolateral medulla (RVLM) presympathetic neurons ( Karlen-Amarante et al, 2023 ) via excitatory and inhibitory inputs from respiratory rhythmogenic networks ( Lipski et al, 1996 ; Molkov et al, 2011 ; Moraes et al, 2012 , 2013 ). However, the exact neuronal mechanisms underlying respiratory modulation of sympathetic activity remain to be characterized.…”
Section: Introductionmentioning
confidence: 99%